2011
DOI: 10.1088/0256-307x/28/6/067104
|View full text |Cite
|
Sign up to set email alerts
|

Voronoi Structural Evolution of Bulk Silicon upon Melting

Abstract: The Voronoi structural evolution of silicon upon melting is investigated using a molecular dynamics simulation. At temperatures below the melting point, the solid state system is identified to have a four-fold coordination structure ⟨4, 0, 0, 0⟩. As the temperature increases, the five-fold coordination ⟨2, 3, 0, 0⟩ and six-fold coordination structures ⟨2, 2, 2, 0⟩ and ⟨0, 6, 0, 0⟩ are observed. This is explained in terms of increasing atomic displacement due to thermal motion and the trapping of the moving ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The Voronoi polyhedron method has been proven to be effective for the analyses of local atomic environment 31 and the volume of cluster 32 in liquids and glasses. The Voronoi index is expressed as < n 1 ,n 2 ,n 3 ,n 4 >, where n i denotes the number of i -edged faces of the Voronoi polyhedrons 33 34 35 . Figure 5 shows the voronoi structure obtained from four typical cooling rates (a) cr1 = 5 × 10 10 K/s, (b) Cr3 = 5 × 10 11 K/s, (c) Cr6 = 1 × 10 13 K/s and (d) Cr8 = 1 × 10 14 K/s.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Voronoi polyhedron method has been proven to be effective for the analyses of local atomic environment 31 and the volume of cluster 32 in liquids and glasses. The Voronoi index is expressed as < n 1 ,n 2 ,n 3 ,n 4 >, where n i denotes the number of i -edged faces of the Voronoi polyhedrons 33 34 35 . Figure 5 shows the voronoi structure obtained from four typical cooling rates (a) cr1 = 5 × 10 10 K/s, (b) Cr3 = 5 × 10 11 K/s, (c) Cr6 = 1 × 10 13 K/s and (d) Cr8 = 1 × 10 14 K/s.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous wrok 33 , it was shown that the <4, 0, 0, 0> is the diamond crystal structure and existed in the crystal silicon. This structure makes the crystal silicon show semiconducting behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations